Cyberbullying: In defense of a preventive perspective - Cordeiro, Leandra (2017)
The Cyberbullying involves the use of information and comunication technologies to humiliate and to attack purposely other and/or others, always with hostile intentions.To realize if the children knows what is the Cyberbullying; if they suffer of Cyberbullying and what they do in a situation like this; to understand if the parents do contact the school when they notice that their children are victims of Cyberbullying and to understand what are the methods often used in these situations.